Delivery in a Female Bladder Exstrophy Patient With Ileal W Pouch Continent Cutaneous Stoma - Zulfiqar, Yevri; Myh, Etrivel; Yusrawati, Yusrawati; Serudji, Joserizal; Wahyudi, Irfan; Rodjani, Arry (Open Access Macedonian Journal of Medical Sciences, 2022)
Propose: To deliver a case report of female bladder exstrophy patients who experienced pregnancy until the birth process. Methods: A 28-year-old woman with a history of bladder exstrophy, which received inadequate treatment during childhood, had bladder shrinkage and uterine prolapse. The patient underwent reconstruction of continent cutaneous stoma and sacrocolpopexy with mesh in her adulthood. She achieved complete continence by intermittent self-catheterization and gained a better quality of life. She later got married and became pregnant. Pregnancy monitoring was done to evaluate the condition of the patient and her fetus. A collaborative team was built to discuss the best option for delivering the procedure. At 38–39 weeks of gestational age, an elective cesarian section was performed to deliver the baby. Results: Despite having a greater risk of complications, a woman with a history of bladder exstrophy could undergo pregnancy and give birth. The choice of delivery, either vaginal or cesarean section, is feasible for delivery. Conclusions: An adult female with bladder exstrophy underwent pregnancy and gave birth. Prior surgery and increased risk of obstetrical complications must be considered.